In-State College Enrollment and Later Life Location Decisions - John V. Winters (Institute of Labor Economics (IZA), 2018)
State and local policymakers are very interested in how attending college in one's home state affects the likelihood of living in that state after college. This paper uses cohort-level data from the American Community Survey, decennial censuses, and other sources to examine how birth-state college enrollment affects birth-state residence several years later. Ordinary least squares and instrumental variables estimates both suggest a statistically significant positive relationship. The preferred instrumental variable estimates suggest that a one percentage point increase in birth-state enrollment rates increases later life birth-state residence by roughly 0.41 percentage points. Implications for policy are discussed.
Keywords: H75; I25; J24; R23; 330; higher education policy; in-state college enrollment; migration; college attendance